2015
DOI: 10.1055/s-0035-1559604
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Supplementation and the Effects on Reproductive Outcomes, Biomarkers of Inflammation, and Oxidative Stress in Women with Polycystic Ovary Syndrome

Abstract: Selenium supplementation could be effective on reproductive outcomes, biomarkers of inflammation, and oxidative stress among women with polycystic ovary syndrome (PCOS). The aim of the study was to determine the effects of selenium supplementation on reproductive outcomes, biomarkers of inflammation, and oxidative stress in PCOS patients. The present randomized double-blind, placebo-controlled trial was conducted on 64 women aged 18?40 years old with PCOS at the clinic affiliated to Ardabil University of Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 56 publications
5
61
1
Order By: Relevance
“…Supplementation with selenium seems to strengthen cellular immunity by the following mechanisms: (i) it upregulates the expression of the T‐cell high‐affinity interleukin‐2 receptor and provides a vehicle for enhanced T‐cell responses; and (ii) it prevents oxidative stress‐induced damage to immune cells . The result of our meta‐analysis is in keeping with the studies suggesting that zinc or selenium supplementation could become an adjuvant therapy for the AA patients. Recent studies found that combination therapy with immunomodulators may be administrated to facilitate enhanced zinc‐targeted action, as immunomodulatory therapy may promote tissue zinc redistribution by decreasing the perifollicular CD8 + T‐cell infiltrate .…”
Section: Discussionsupporting
confidence: 83%
“…Supplementation with selenium seems to strengthen cellular immunity by the following mechanisms: (i) it upregulates the expression of the T‐cell high‐affinity interleukin‐2 receptor and provides a vehicle for enhanced T‐cell responses; and (ii) it prevents oxidative stress‐induced damage to immune cells . The result of our meta‐analysis is in keeping with the studies suggesting that zinc or selenium supplementation could become an adjuvant therapy for the AA patients. Recent studies found that combination therapy with immunomodulators may be administrated to facilitate enhanced zinc‐targeted action, as immunomodulatory therapy may promote tissue zinc redistribution by decreasing the perifollicular CD8 + T‐cell infiltrate .…”
Section: Discussionsupporting
confidence: 83%
“…The present study has demonstrated that selenium supplementation in patients with T2DM and CHD resulted in a significant decrease in serum hs-CRP, but did not affect plasma NO concentrations compared with the placebo. In line with our findings, supplementation with daily one selenplus capsule containing 50 μg selenium, 8 mg zinc, 400 μg vitamin A, 125 mg vitamin C, and 40 mg vitamin E among rheumatoid arthritis patients [40] and 200 μg selenium among PCOS women [41] resulted in a significant decrease in hs-CRP concentrations among rheumatoid arthritis patients for 12 weeks. Similar relationships between plasma selenium and CRP concentration have also been reported previously in septic patients [42].…”
supporting
confidence: 90%
“…MetS is associated with increased risk of CVD, T2DM, and allcause mortality [2]. In addition, subjects with PCOS and/or diabetes are susceptible to metabolic disorders [18,23,25,26]. Our meta-analysis of RCTs supported that selenium supplementation resulted in a significant decrease in insulin, and a significant increase in QUICKI, but unchanged FPG and HOMA-IR.…”
Section: Discussionsupporting
confidence: 55%